Artificial general intelligence : 6th International Conference, AGI 2013, Beijing, China, July 31 - August 3, 2013 Proceedings - Rudolph, Sebastian; Wang, Pei; Kuhnberger, Kai-Uwe (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Artificial General Intelligence, AGI 2013, held in Beijing, China, in July/August 2013. The 23 papers (17 full papers, 3 technical communications, and 3 special session papers) were carefully reviewed and selected from various submissions. The volume collects the current research endeavors devoted to develop formalisms, algorithms, and models, as well as systems that are targeted at general intelligence. Similar to the predecessor AGI conferences, researchers proposed different methodologies and techniques in order to bridge the gap between forms of specialized intelligence and general intelligence.